Jesus and Gospel - Stanton, Graham (Cambridge University Press, 2004)
Jesus and Gospel -- The fourfold Gospel -- Jesus traditions and Gospels in Justin Martyr and Irenaeus -- The law of Christ and the Gospel -- Jesus of Nazareth, a magician and a false prophet who deceived God's people? -- Early objections to the resurrection of Jesus -- Why were early Christians addicted to the Codex? -- What are the Gospels? New evidence from papyri?